2023
DOI: 10.1038/s41598-023-45483-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of restrictive cumulative fluid balance on 28-day survival in invasively ventilated patients with moderate to severe ARDS due to COVID-19

Ricardo Esper Treml,
Tulio Caldonazo,
Pedro Hilton A. Filho
et al.

Abstract: This study aimed to evaluate the effect of two restrictive cumulative fluid balance (CFB) trends on survival and on major clinical outcomes in invasively ventilated patients with moderate to severe respiratory distress syndrome (ARDS) due to SARS-CoV-2. Prospective data collection was conducted on patients in the intensive care unit (ICU) originating from a tertiary university hospital. The primary outcomes were the risk association between the CFB trend during D0 to D7 and 28-day survival. The secondary outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Further, this group showed worse respiratory parameters as higher needs of FiO 2 and PEEP than those with lesser lung parenchymal involvement. Our findings were comparable to the multicenter observational study PRoVENT-COVID-19 and other studies which showed worse pulmonary parameters in critically ill patients with COVID-19 with severe lung involvement, especially in patients with more than 40% lung parenchyma involvement [ 3 , 32 , 33 ]. The results obtained may serve as a confirmation of the utility of Chest-CTSS) in predicting respiratory outcomes among critically ill patients with COVID-19 in the ICU setting.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Further, this group showed worse respiratory parameters as higher needs of FiO 2 and PEEP than those with lesser lung parenchymal involvement. Our findings were comparable to the multicenter observational study PRoVENT-COVID-19 and other studies which showed worse pulmonary parameters in critically ill patients with COVID-19 with severe lung involvement, especially in patients with more than 40% lung parenchyma involvement [ 3 , 32 , 33 ]. The results obtained may serve as a confirmation of the utility of Chest-CTSS) in predicting respiratory outcomes among critically ill patients with COVID-19 in the ICU setting.…”
Section: Discussionsupporting
confidence: 90%
“…critically ill patients with COVID-19 with severe lung involvement, especially in patients with more than 40% lung parenchyma involvement [3,32,33]. The results obtained may serve as a confirmation of the utility of Chest-CTSS) in predicting respiratory outcomes among critically ill patients with COVID-19 in the ICU setting.…”
Section: Plos Onementioning
confidence: 61%